Corporate Manslaughter by Industrial Robots at Work: Who Should Go on Trial under the Principles of Common Law Australia? - Solaiman, S.M. (Journal of Law and Commerce, 2017)
Industrial robots have been increasingly used for decades and the International Federation of Robotics predicts that 1.3 million more of such humanoids will be installed in factories across the globe between 2015 and 2018. While robots are deemed beneficial for industrial production, they pose a serious threat to our health and safety. Meanwhile, robots have killed many people and gravely injured numerous others in different countries. Policymakers around the world remain largely unmoved about resolving the uncertainty over the specificity of which persons should go on trial for such killings. This article examines the principles of common law governing manslaughter by criminal negligence with particular reference to Australia; however, it will generally apply to other common law countries as well. It finds that while it would be theoretically possible to identify the potential accused of workplace deaths caused by robots, we consider that the common law identification doctrine in practice will be a bar to successful prosecutions against corporate employers given the specific complexities associated with the usage of industrial robots. This article therefore submits a recommendation with justifications for dealing with this serious offence by enacting appropriate manslaughter law for the effective regulation of robots provoked fatalities.